Brachioradial Artery (BRA) & Superficial Brachioulnar Artery (SBUA): a case report - Saharudin, Shahida; Lwin, San San; Aung, Htar Htar; Sa'at@Yusof, Azlin (2013)
It is no longer uncommon to encounter arterial variants of upper extremities during routine dissection and clinical practice. It has been reported that arterial variations can occur up to 20%. Of these variants, radial and ulnar artery of high origin is quite commonly encountered. We reported a subject with high origin of radial (BRA) and ulnar artery (SBUA) on each side of the upper limb.